Haemoperitonium : A Rare Presentation of Choriocarcinoma (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Gestational choriocarcinoma is one of the most malignant form of group of tumors with almost 100% cure rate, developes secondary to pregnancy (Normal or ectopic) following hydatidiform mole, miscarriage or even after child birth. This starts within the uterus in the placenta but a tendency to metastasize to other parts of the body. Indicative signs are unexplained heavy and irregular uterine bleeding, raised serum b hCG, non normalization of b hCG following abortion or delivery and if it spreads, signs of metastasis. Our study presents a case of Choriocarcinoma presented with haemoperitonium, who was treated successfully with surgical and medical management. A 25 years lady Para 1+0, age of 3 years, normal delivery had an emergency admission for 2 months amenorrhoea with severe lower abdominal pain, slight vaginal bleeding suspected clinically as ruptured ectopic pregnancy. Ultrasonography suggest Invasive mole with huge peritoneal collection. After sending serum b hCG she was treated surgically and per operative findings were in favour of Choriocarcinoma which was confirmed by histopathological reports. Serum b hCG was raised and she was treated with combination (MAC protocol) chemotherapy.Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 57-58